2014
DOI: 10.1155/2014/268967
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Mild Cognitive Impairment Display Reduced Auditory Event-Related Delta Oscillatory Responses

Abstract: Background. Event-related oscillations (ERO) may provide a useful tool for the identification of cognitive deficits in mild cognitive impairment (MCI) and Alzheimer's disease (AD). In the present study, we investigate peak-to-peak amplitude of auditory event-related delta oscillations of MCI subjects. Method. The study included twenty-two consecutive patients with MCI recruited in neurology clinic and 21 age- and education-matched normal elderly controls. A classical auditory oddball paradigm was used in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The frequency pairs that showed significant higher PAC value for MCI compared to NI group are the δ−α 2 , θ−α 2 , θ−β 1 , θ−γ, β 1 −γ and β 2 −γ (Figure 7 ). Previous studies demonstrated a decreased of δ amplitude in auditory tasks for MCI compared to the control group (Yener et al, 2012 ; Başar et al, 2013 ; Yener and Basar, 2013 ; Kurt et al, 2014 ). In this context, the higher coupling of δ phase with θ amplitude in MCI subjects can be interpreted as an increased attention (Dimitriadis et al, 2010a ; Başar et al, 2013 ; Kurt et al, 2014 ).…”
Section: Discussionmentioning
confidence: 86%
“…The frequency pairs that showed significant higher PAC value for MCI compared to NI group are the δ−α 2 , θ−α 2 , θ−β 1 , θ−γ, β 1 −γ and β 2 −γ (Figure 7 ). Previous studies demonstrated a decreased of δ amplitude in auditory tasks for MCI compared to the control group (Yener et al, 2012 ; Başar et al, 2013 ; Yener and Basar, 2013 ; Kurt et al, 2014 ). In this context, the higher coupling of δ phase with θ amplitude in MCI subjects can be interpreted as an increased attention (Dimitriadis et al, 2010a ; Başar et al, 2013 ; Kurt et al, 2014 ).…”
Section: Discussionmentioning
confidence: 86%
“…We analyzed delta, theta, beta and alpha oscillatory responses of some of these subjects as control groups for our studies on mild cognitive impairment Kurt et al, 2014;Yener et al, 2013).…”
Section: Subjectsmentioning
confidence: 99%
“…At this stage, the delta frequency range (0.5-3 Hz) was chosen for investigating the age effect on ERO, since marked differences were observed in delta range in previous studies of our group Kurt et al, 2014;Yener et al, 2008Yener et al, , 2013. Peak-to-peak amplitude of delta target ERO responses during the post-stimulus 0-800 ms time window of two groups of elderly was measured.…”
Section: Digitally Filtered Event-related Delta Oscillatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…ERPs have been largely applied for scientific purpose in cognitive neuroscience but also in clinical application (Niedermeyer and Lopes da Silva, 2005, Kurt et al, 2014, Polak et al, 2014). An excellent example of this are the olfactory ERPs now widely used for assessment of olfactory functions, e.g.…”
Section: Q6mentioning
confidence: 99%